Antimicrobial activity of curry leaves (Murayya koenigii) on selected foodborne pathogens / Bazlee Abu Bakar, Wan Razarinah Wan Abdul Razak and Che Puteh Osman - Abu Bakar, Bazlee; Wan Abdul Razak, Wan Razarinah; Osman, Che Puteh (Faculty of Applied Sciences, 2020)
Food poisoning is one of the most common diseases in the world in which are caused by ingesting foodborne pathogens. Study was conducted to determine the antimicrobial activity of Murayya koenigii leaves extract on foodborne pathogens namely Salmonella typhi ATCC 14028, Staphylococcus aureus ATCC 25923, Bacillus cereus ATCC 11778, Escherichia coli ATCC 25922, Candida albicans ATCC 10231 and Aspergillus niger ATCC 16404. The antimicrobial activity was determined at four different concentrations of 150 mg/mL, 200 mg/mL, 250 mg/mL and 300 mg/mL S. typhi was the most sensitive to M. koenigii extract at concentration 300 mg/mL with zone of inhibition diameter mean value of 8.67 ± 0.67 mm followed by E. coli, S. aureus and B. cereus with zone of inhibition diameter mean values of 8.33 ± 0.88 mm, 8.00 ± 0 mm and 7.67 ± 0.33 mm. C. albicans and A. niger were resistant to the extract. The minimum inhibitory concentrations (MICs) and minimum bactericidal concentrations (MBCs) against S. typhi, S. aureus, B. cereus and E. coli were 75 mg/mL, 150 mg/mL 125 mg/mL and 100 mg/mL respectively. There were no significant differences on the concentrations of M. koenigii extract on the zone of inhibition diameter produced (p=0.056). M. koenigii leaves extract exhibit antibacterial activity but no antifungal activity.